Teachers’ Professional Development at Public Campuses in Nepal: Policies and Practices - Panthee, Dinesh (Kaladarpan कलादर्पण, 2023)
Teacher professional development (TPD) is the process of making teachers competent at applying the knowledge and skills they have attained in the classroom practice. TPD keeps academics up-to-date with the changing world and knowledge. The objective of this study was to explore policies and practices of teacher professional development in public campuses of Nepal. This study was qualitative approach with a phenomenological design. The participants of the study were three teachers of different public campuses of Rupendehi district selected purposively. The study revealed TPD policies as opportunities for teachers of public campuses deserve high consequence in the sense that they help teachers develop various kinds of professional skills, knowledge, new techniques of teaching. However, Public campuses are facing many challenges which include proper management TPD for faculties of their campuses and there is a gap between policies and practices in implementation of TPD in public campuses of Nepal.